Humanitas: uma leitura do significado machadiano no filme Quanto vale ou é por quilo? - Brito, Amanda Ramalho de Freitas (2013)
Adaptation is one more artistic resource used in cinema to show a fictitious story. The word show also means tell, but it is employed by Linda Hutcheon (2011) when she refers to cinema, by considering it a performance art which has a process of representation centred on the speech of characters played by actors, the actions, sounds and visual images. The process of adaptation has been a resource used in art throughout mankind s history. The symbolist picture in Ofélia (1851), by John Everett Millais, for instance, is a plastic adaptation depicting the death of the Shakespearean character ( Hamlet ). The process of adaptation is a very interesting resource due to the fact that it makes us think of the approximation between different semiotic systems and helps us to observe how one narrative way acquires signification from another. Thus, our work is a study on the short story called Father against mother (1906), by Machado de Assis, and its free adaptation called How much is it or is it by the kilo? (2004), by Sérgio Bianchi. Through a analytical study, we endeavoured to investigate how the Machado de Assis topos fight for survival , symbolized by the predatory relationship and contradiction ( represented by the characters ) is transcoded in the diegetic space of the film. With this in mind, we attempted to observe stylistic features, such as irony, pessimism and realism, as well as structural aspects: characters, time and focus. This category was promptly characterized in our analysis as the narrative element which enabled us to reflect on the film creative process. In order to analyse the function of the narrative focus, we based our assumptions on authors who study the narrative categories in literature, such as Norman Friedman (2002) and mainly Gérard Genette (1989); also Francis Vanoye and Anne Goliot-Lété (1994) and Marcel Martin (2003) who particularly study the narrative focus in cinematographic language.